Equal opportunities for women and men in the European Union : annual report 1997. (Employment and social affairs, 1998)
This annual report on equal opportunities for women and men in the European Union presents an overview of the main developments which have had an impact on equal opportunities at community and at national level during 1997. While important issues arose across a range of areas, three developments deserve to be particularly highlighted: the Amsterdam Treaty was agreed with new powers relating to equal opportunities; the Member States jointly decided to put in place a new employment strategy, for immediate implementation, in which equal opportunities is an explicit and important component; progress was made in integrating equal opportunities for women and men into other policy areas, building on the commitments as regards mainstreaming.